GE_GERICHTE C/28664/2019 vom 15. Oktober 2024 - GE Cour de justice (2024)
DIVORCE;LIQUIDATION DU RÉGIME MATRIMONIAL;PRÉVOYANCE PROFESSIONNELLE;OBLIGATION D'ENTRETIEN;ENFANT;MINORITÉ(ÂGE);CONJOINT;RENTE D'INVALIDITÉ;ATTEINTE À LA SANTÉ